MSME taxpayer compliance in Pekanbaru from the perspective of tax understanding, tax sanctions and tax socialization - Angelina, Vivian; Jayanto, Veronica; Firmansyah, Amrie; Trisnawati, Estralita (Educoretax, 2024)
The tax authorities in Indonesia continue to make extensive efforts to increase tax revenue, which is the main source of state revenue. This extensification focuses on increasing individual tax revenue, especially in the Micro, Small, and Medium Enterprises (MSMEs) sector. This study aims to analyze the effect of tax understanding, tax sanctions, and tax socialization on the level of taxpayer compliance of MSMEs in Pekanbaru. The study uses a quantitative method with the Structural Equation Model (SEM) approach. Data were obtained through an online questionnaire survey from MSME business actors in Pekanbaru City. A purposive sampling technique was used to select 32 respondents as research samples. The sample criteria include business actors domiciled in Pekanbaru who calculate and pay taxes independently and meet MSME criteria based on applicable regulations. The study results indicate that tax understanding and tax sanctions positively affect the level of taxpayer compliance of MSMEs in Pekanbaru. However, tax socialization does not show a significant effect on taxpayer compliance. This study provides insight into tax compliance patterns outside Java that can be considered when making regulations by the tax authorities in Indonesia.